Strategi Guru dalam Pembentukan Karakter Santri Madrasah Aliyah Swasta Pesantren Jabal Nur Aceh Utara - Mauliani, Mauliani; Musdar, Musdar (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2025)
The formation of students’ character in pesantren represents a crucial issue in contemporary Islamic education, particularly in facing the challenges of modernization and globalization. Madrasah Aliyah Swasta (MAS) Jabal Nur stands as an example of an institution that integrates religiosity, discipline, and diverse learning methods in shaping students’ personalities. This study seeks to analyze the character education strategies implemented in the pesantren. Employing a descriptive qualitative approach, data were collected through observation, in-depth interviews with teachers and students, as well as documentation of learning activities. Data were analysed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, with validity reinforced through source triangulation. The findings reveal three major points. First, religiosity is cultivated through daily worship practices such as collective prayers, congregational worship, and dhikr, which are integrated into learning activities. Second, the teacher-student relationship is characterized by personal attention, emotional communication, and intensive guidance that creates a supportive learning climate. Third, the use of varied teaching methods such as lectures, question-and-answer, practice, and assignments enhances students’ engagement. The impact is evident in students becoming more religious, disciplined, independent, and orderly. These findings affirm that character formation in pesantren is shaped not only through structural regulations but also through collective culture, teachers’ role modelling, and affective daily interactions. This study aligns with the theories of value internalization, pedagogy of care, and social learning, while enriching the contemporary literature on character education in pesantren. Thus, pesantren remain relevant as a holistic, adaptive, and sustainable model of Islamic education.